Thriving in the Rain: Natural Shocks, Time Allocation, and Women's Empowerment in Bangladesh - Sveva Vitellozzi; Gianna Claudia Giannelli (Institute of Labor Economics (IZA), 2023)
In low- and middle-income countries, differences between men and women in their time use patterns represent a major source of gender inequality. Among other factors, natural shocks can contribute to the widening of these differences. This paper examines the impact of the 2017 flood in Bangladesh on men's and women's time use patterns and women's empowerment. Using georeferenced and longitudinal data, we find that the flood decreased women's time spent on domestic work while increasing their engagement in paid activities and empowerment. In contrast, men spent less time at work and increased their participation in housework to substitute for women's domestic work. These responses to the shock are confirmed only for those individuals who were exposed to another flooding event that occurred in 2014. To better understand the underlying mechanisms, we look at the medium-term impact of the 2014 flood on women's empowerment and on their engagement in paid activities, and we find that the shock still positively affects both variables, suggesting that when endogenous, an increase in empowerment persists over time and influences reactions to the 2017 shock.
Keywords: J16; J22; J43; 330; time allocation; time poverty; natural shocks; women's empowerment